2020
DOI: 10.1155/2020/7347298
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated Expression of linc-ROR in Gastric Cancer and Its Potential Diagnostic and Prognosis Value

Abstract: Background. Gastric cancer (GC) is one of the global mortality diseases and has a poor prognosis due to the lack of ideal tumor biomarkers. Numerous studies have shown that long noncoding RNAs (lncRNAs) can affect the occurrence and development of cancer through a variety of signaling pathways. The abnormal expression and specificity of lncRNAs in tumors make them potential biomarkers of cancers. Nevertheless, the diagnostic roles of lncRNAs in GC have been poorly understood. So this study focuses on the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
1
6
1
Order By: Relevance
“…The obtained AUC value for LINC-ROR in the current study is comparable with Yu et al. study [ 18 ], yet the specificity of this marker in our study is far beyond their study [ 18 ]. However, the AUC value obtained for combination of two lncRNAs was not high enough.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The obtained AUC value for LINC-ROR in the current study is comparable with Yu et al. study [ 18 ], yet the specificity of this marker in our study is far beyond their study [ 18 ]. However, the AUC value obtained for combination of two lncRNAs was not high enough.…”
Section: Discussionsupporting
confidence: 90%
“…have reported down-regulation of LINC-ROR in gastric cancer tissues compared with their nearby non-tumor tissues. Notably, expression of this lncRNA has been associated with tumor differentiation [ 18 ]. LINC-ROR expression has been previously assessed in a cohort of Iranian patients with diverse types of cancers revealing its up-regulation in esophageal, ovarian, and cervical cancers, while being down-regulated in breast, sarcoma, colon, and melanoma patients [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al indicated that the high expression of SCD1 might predict poor prognosis in gastric cancer patients, but the AUC value at 1-, 3-, and 5-year survival rates were 0.557, 0.569, and 0.595, respectively (26), were significantly lower than the results of our study. In addition, the AUC's value of another predictive biomaker (linc-ROR) was 0.6495 (27), which was also lower than ours. So, we proposed that our findings improved the prediction accuracy for the prognosis of gastric cancer patients.…”
Section: Discussioncontrasting
confidence: 83%
“…We assessed the quality of included studies using NOS and found that the quality of the enrolled studies was acceptable. Thirty-eight studies [ 9 , 12 , 14 , 21 27 , 29 31 , 33 , 34 , 36 , 38 40 , 42 , 46 50 , 52 55 , 57 , 62 , 63 , 65 , 66 ] were of high quality while the other 16 studies [ 28 , 32 , 35 , 37 , 41 , 43 , 47 , 51 , 56 , 58 61 , 64 , 67 ] were of moderate quality.…”
Section: Resultsmentioning
confidence: 99%